The Gravity Model on EU Countries – An Econometric Approach - Marku, Megi (European Journal of Sustainable Development, 2014)
Foreign Direct Investment, play a huge role in the growth of the global businesses. They can provide to a firm, new markets where the firm can operate, new marketing channels, manufacturing facilities, access to technology and to the products, and they also provide techniques and funds previously unknown. For the host country, this source of technologies, capital, processes, techniques, and managerial skills can provide an important impetus to the economic development of the country. Through this study, it has been analyzed how FDI are affected by the distance and by the economic size of the country. Given that such a gravity model (size and distance) on FDI already exists, this research has examined particularly the impact of these two factors on FDI of the EU member states. Through an econometric model it has been examined how economic size and distance affect foreign investment of EU leading countries in some of the world states and which of two factors have had the greatest impact. The hypothesis raised in this paper is related to the fact that the gravity model with its factors is extremely important for the volume of FDI, the size playing a more important role than the distance. By using statistical judgment and econometric analysis it has been explored if the hypothesis rose above, is statistically valid or not. From the model resulted that the impact of the size coefficient on FDI is 0.0042 million Euros, while the distance coefficient is – 0.36 millions. It shows that with the increase of GDP and the distance between countries, FDI increase and decrease respectively with the above coefficients. According to statistical methods of control, economic size was a more determinant factor than the distance, giving us the idea that in recent years with the increased role of globalization the importance of distance has significantly decreased. In this paper it is recommended the gravity models should consider a lot other factors besides size and distance. JEL classification: A1, C01, C12, C31, C51, F21 Keywords: FDI, international trade, gravity model, EU countries, econometric model.